A complex encoding flower pollination algorithm for constrained engineering optimisation problems. (2017) - Abdel-Baset, Mohamed; Wu, Haizhou; Zhou, Yongquan
In this paper, we apply a complex encoding flower pollination algorithm (CEFPA) to solve constrained engineering optimisation problems. The performance of the proposed algorithm is tested using five standard benchmark functions and four engineering problems. A comparative study of the results with those obtained well-known algorithms is used to validate and verify the efficiency of CEFPA. The CEFPA performs expressively better in terms of the speed and stability for the optimal solution.